2023
DOI: 10.35693/2500-1388-2023-8-3-169-175
|View full text |Cite
|
Sign up to set email alerts
|

Dependence in instrumental activities of daily living and its associations with other geriatric syndromes in people over 65 years of age: data from the Russian epidemiological study EUCALYPT

Natalya V. Sharashkina,
Natalya M. Vorobyeva,
Irina V. Permikina
et al.

Abstract: Aim to assess the frequency of disability in instrumental activities of daily living (IADLs) and to analyze its associations with other geriatric syndromes in persons aged 65 years. Material and methods. The study involved 4,308 people (30% male) living in 11 regions of the Russian Federation, aged 65 to 107 years (average age 78 8 years). The majority (60%) of participants were examined in a polyclinic, every fifth in a hospital (20%) or at home (19%), 1% in nursing homes. All patients underwent a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Zheng et al 10) examined cognitive function trajectories in people aged 54-85 years, reporting that at the cohort level, cognitive functioning showed accelerating deterioration with age. Regarding disability in instrumental activities of daily living (IADLs), Sharashkina et al 11) found that the prevalence of IADL dependence increased significantly with age in adults > 65 years. In particular, 82.3% of people over the age of 85 years showed dependence in IADLs, compared to only 33% and 54.2% of those aged 65-74 years and 75-84 years, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al 10) examined cognitive function trajectories in people aged 54-85 years, reporting that at the cohort level, cognitive functioning showed accelerating deterioration with age. Regarding disability in instrumental activities of daily living (IADLs), Sharashkina et al 11) found that the prevalence of IADL dependence increased significantly with age in adults > 65 years. In particular, 82.3% of people over the age of 85 years showed dependence in IADLs, compared to only 33% and 54.2% of those aged 65-74 years and 75-84 years, respectively.…”
Section: Introductionmentioning
confidence: 99%